RECONSTRUCTION OF CRIMINAL SANCTIONS AGAINST CRIME OF ACTORS AND MURDER MURDER IN PLAN BASED ON VALUE OF JUSTICE CRIMINAL CODE - Maria Marghareta Titiek Pudji Angesti Rahayu; Teguh Prasetyo; Sri Endah Wahyuningsih (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The increasing crime rate is influenced by several factors, from the nature of public welfare, until the little things like a matter of feelings. Indonesia as a country with dignity ensure the protection of the lives of every citizen, from being in the womb until the death. The results of this study were 1) In terms of Article 340 of the Criminal Code is a murder with the most severe criminal penalty, the death penalty. 2) The court's decision is considered to have a fair especially criminal sanctions imposed on the perpetrators, because it is actually the most disadvantaged in the event of a criminal offense is murder victim's family. 3) The murder plan to enter in the category of elements of murder which in the case of positive criminal law, Killing positive in the context of criminal law, categorized for the murder foreseen by the perpetrator, the murder because of persecution and murder due to negligence or neglect. Keywords: Reconstruction of Criminal Sanctions, Against Perpetrators of the Crime of Murder, Value of Justice.